Enzymatic and Oxidizing Agents for the Decomposition of Polymers Used in the Composition of Drilling Muds - Małgorzata Uliasz; Grzegorz Zima; Sławomir Błaż; Bartłomiej Jasiński (Energies, 2021)
The article presents the results of research on the influence of enzymatic and oxidizing agents on polymers used in drilling mud technology. The research used calcium hypochlorite, urea peroxide, sodium persulfate, amylase and cellulase. This allowed us to determine the optimal concentrations of these agents in order to reduce the rheological parameters of drilling muds. The ability of enzymes and oxidants to decompose colloids used in the composition of drilling muds was determined on the basis of measurements of their rheological parameters and the influence of oxidants and enzymes on the properties of filter cakes. The final effect of the presented research was the development of a drilling mud treatment method before the cementing procedure and the development of washer fluids containing enzymatic or oxidizing agents to be used to prepare the borehole for the cementing procedure. The drilling muds selected for the research contained starch and cellulose polymer colloids, which allowed for the selection of appropriate agents depending on the type of polymer set used in the drilling mud. Positive results were obtained regarding the possibility of thinning the drilling mud immediately before cementing, as well as the possibility of using oxidants and enzymes in the composition of washer fluids.